Assessing Environmental Concerns and Their Effects on Customer Satisfaction with Petrol Scooters - Hamal, Bikit (NPRC Journal of Multidisciplinary Research, 2024)
Background: This study investigates customer satisfaction regarding petrol scooters, reflecting a shift in market dynamics from a buyer's market to a seller's market, characterized by increased competition and consumer choice. Understanding consumer satisfaction is vital for manufacturers to enhance loyalty and retain customers in this evolving landscape. Objective: The primary objective of this research is to evaluate consumer perceptions of petrol scooters in terms of performance, pricing, service availability, and environmental impact. Specifically, it aims to identify the factors that contribute to customer satisfaction and the expectations users have regarding their scooters. Methods: A quantitative research approach was employed, utilizing a structured questionnaire with a five-point Likert scale. The survey was distributed among 116 respondents, focusing on their experiences and satisfaction levels with petrol scooters. Findings: The results reveal that a significant portion of the scooter-riding population is young females aged 18-25, with 44.8% using their scooters daily. While many users express satisfaction with their scooters, they also identify areas for improvement, such as speed, fuel efficiency, noise, and lighting. Conclusion: The study concludes that enhancing these features can bolster customer satisfaction, particularly among young women, thereby promoting brand loyalty and encouraging repeat purchases. Manufacturers should focus on these improvements to align with consumer expectations and preferences. Novelty: The novelty of this research lies in its focus on the unique preferences of young female riders in the petrol scooter market, offering actionable insights for manufacturers to tailor their marketing strategies effectively.